RESTAURANT MARKETING STRATEGIES IN FACING NEW HABITS POST-COVID-19 PANDEMIC: REVOLUTIONARY ENTREPRENEUR PARADIGM - Marika Christa Widyasari; Harry Soesanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The Covid-19 pandemic is a form of danger that has the potential to threaten all aspects of peo-ple's lives, such as social, economic, health and psychological. The impact on people in Indone-sia is of course not much different from people in other countries who are also facing the Covid-19 pandemic. The condition of social vulnerability (social vulnerability) is a real reality that occurs in society in the face of the Covid-19 pandemic. Social vulnerability has shocked the resilience of society due to the Covid-19 pandemic.The Covid 19 pandemic has made the economy in Indone-sia sluggish, especially for SMEs. Even though the existence of SMEs in Indonesia is very im-portant and considered by the government because SMEs can accommodate a large number of workers and become a source of income for the middle and lower classes of the community. The productivity of SMEs in an area will undoubtedly have an impact on job availability, and of course, it will reduce the number of unemployed Therefore, this study looks at how to improve the performance of SMEs so that they exist in the midst of the Covid 19 pandemic. The cases of the Covid-19 pandemic in Indonesia continue to increase every day. As of March 30, 2020, there were 1,414 positive cases, 75 recovered cases, and 122 deaths. The Covid-19 pandemic in Indonesia has a multi-sectoral impact, from health, education, social, economy, to religious activities in the community. The impact on these sectors is increasingly being felt by the community, especially in relation to the issue of social welfare in society. The social welfare of the community here is relat-ed to health, household economic conditions, a sense of security, comfort and a good quality of life. So that people who are faced with the Covid-19 pandemic can still fulfill their basic needs and carry out their social functions. That is why, apart from being the main focus of dealing with the Covid-19 pandemic, the government has not ruled out the welfare conditions of the communi-ty during the Covid-19 pandemic. If the people's welfare is neglected, it is feared that it will trigger massive social vulnerability in the community. This of course makes the situation and conditions in Indonesia even more like tangled threads. Solve one problem, another problem arises.